42nd International Conference on Environmental Systems 2012
DOI: 10.2514/6.2012-3642
|View full text |Cite
|
Sign up to set email alerts
|

Development of Carbon Dioxide Removal Systems for Advanced Exploration Systems

Abstract: "NASA's Advanced Exploration Systems (AES) program is pioneering new approaches for rapidly developing prototype systems, demonstrating key capabilities, and validating operational concepts for future human missions beyond Earth orbit" (NASA 2012). These forays beyond the confines of earth's gravity will place unprecedented demands on launch systems. They must not only blast out of earth's gravity well as during the Apollo moon missions, but also launch the supplies needed to sustain a crew over longer periods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 6 publications
0
31
0
Order By: Relevance
“…In test, a Catacel structured sorbent demonstrated slightly less CO2 removal rates than 4 kg/day of 2630 ppm CO2 using a high temperature of 170°C, a low pressure of only 0.4 psia and a rather slow cool down rate. These positive results show that the notion of a structured sorbent as a drop-in bed replacement for 4-Bed CO2 Scrubber is possible [9]. The LSS project plans for continued technological investment in FY2019.…”
Section: Structured Sorbentsmentioning
confidence: 88%
See 1 more Smart Citation
“…In test, a Catacel structured sorbent demonstrated slightly less CO2 removal rates than 4 kg/day of 2630 ppm CO2 using a high temperature of 170°C, a low pressure of only 0.4 psia and a rather slow cool down rate. These positive results show that the notion of a structured sorbent as a drop-in bed replacement for 4-Bed CO2 Scrubber is possible [9]. The LSS project plans for continued technological investment in FY2019.…”
Section: Structured Sorbentsmentioning
confidence: 88%
“…The Structured Sorbents task intends to design a temperature swing adsorption (TSA) process that utilizes a structured 13X zeolite sorbent, ideally as a replacement for the 4-Bed CO2 Scrubber zeolite adsorbent bed. The 4-Bed CO2 Scrubber is a carbon dioxide removal system intended for demonstration on ISS in 2020 [9]. Structured adsorbents, when compared to packed beds, have lower pressure drop, higher mass transfer rates, resist fluidization and demonstrate improved thermal management.…”
Section: Structured Sorbentsmentioning
confidence: 99%
“…5. Comparative analyses of zeolites UOP RK-38 and UOP ASRT has shown that the RK-38 has an improved CO 2 removal capacity under ISS CDRA operational conditions. TGA, breakthrough, and equilibrium capacity testing all indicated an increased capacity.…”
Section: Development and Test Of A Third-scale Isothermal Bulk Desiccmentioning
confidence: 97%
“…Testing verified that the previous insulation, alumina paper, was neither thick enough nor compliant enough to prevent flow between the edge of the jelly roll and the ceramic plate. 2 More recently the adsorber was disassembled for visual inspection of the insulation, and replacement with a thicker, more compliant type. Follow-on velocity measurements confirmed that the bypass was virtually eliminated.…”
Section: Analysis and Testingmentioning
confidence: 99%
“…This lack of a consensus delays the start of significant vehicle and systems development, demonstrating the need of the flexible path approach and the ability to support multiple destinations with a common architecture and technology base. For systems such as ECLSS that require long lead times for technology maturation, systems development must start in the very near future in order to deploy usable and reliable systems in the intermediate (5)(6)(7)(8)(9)(10) year) future. Applying the flexible path philosophy will allow ECLSS development to commence absent a specific mission plan and destination goal.…”
Section: American Institute Of Aeronautics and Astronauticsmentioning
confidence: 99%